Contraception Knowledge, Contraception Self-Efficacy among University Students - Kang, Gyun-Young; Kim, Jinju (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: This study was attempted to provide university students with basic data necessary for establishing proper contraception knowledge and settling sound sex culture with descriptive research to check the degree of university students' contraception knowledge and contraception self-efficacy.Methods/Statistical analysis: The subjects of this study were 458 first-year students of a university and the data were collected from May 1 to May 20, 2019. The collected data were analyzed by t-test, ANOVA, Pearson's correction, x² test, and multiple progress analysis. According to the research,Findings: University students had 8.87 points for contraception knowledge and 44.68 points for contraception self-efficacy, showing low contraception knowledge and more than moderate of contraception efficacy. The relationship between contraception knowledge and contraception self-efficacy (r=.270, p=.000) has been shown to as positively correlated. The general characteristics that affect the contraception self-efficacy of university students were gender (β=.106 p=.023).Improvements/Applications: Therefore, the development and application of sex education and contraception-related education programs that are viable and suitable for university students to settle sound and healthy sex and sex culture are very necessary.